Ida, Republic County - Durflinger, Kyle P. (Kansas State University, The Chapman Center for Rural Studies, 2012)
The town of Ida, once located in Republic County, Kansas, was created to meet the needs of a growing population in Rose Creek Township. As time progressed and the railroads entered the scene, specifically the Chicago Rock Island, the needs of the surrounding community changed. Ida no longer me the demands of its people and disappeared from the landscape. This study examines early maps of Republic County, photographs of Ida town site and cemetery, and the recorded history from various local sources.
Kyle P. Durflinger, “Ida, Republic County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/96.
Keywords: Big Spring Creek; Anna P. Bobenhouse; Royseville; Republic County; Munden; Odd Fellows